Separate Spheres: the Organization of Work in a Confectionery Factory: Ganong Bros., St. Stephen, New Brunswick - McCallum, Margaret (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1989)
Abstract Ganong bros., a family-owned confectionery factory, is a major employer in a small town in southwestern New Brunswick. Up to the end of the Second World War, the period of this study, the numbers employed in the confectionery industry fluctuated dramatically with the variable seasonal demand for confectionery. At Ganong Bros., less than half the total workforce was employed for more than half the year. Work in the factory was divided along gender lines men made the candy,and women added the finishing touches. About two-thirds of the factory employees were women, most of them young and single. These women could be considered as a reserve army of labour, since many of them worked for a few weeks only, in the busiest season. But when women were not available to fill positions in traditionally female departments, Ganong Bros, management did not consider hiring men instead, even when the women's wages compared favourably to men's. Management decisions about the organization of work in the factory were influenced not only by technical or financial considerations, but by unquestioned assumptions about what work was appropriate to each gender.